(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Neonatal seizures are among the most common neurological emergencies during the neonatal period and are associated with significant morbidity and mortality. They occur more frequently in preterm and low birth weight infants and may result from hypoxic-ischemic encephalopathy, metabolic disturbances, central nervous system infections, intracranial hemorrhage, and congenital brain abnormalities. Early diagnosis remains challenging because normal neonatal movements may resemble seizures. Delayed recognition and treatment may adversely affect neurological outcomes, leading to epilepsy, cerebral palsy, developmental delay, and intellectual disability. Objective: To determine the frequency and outcomes of neonatal seizures among neonates admitted to the Neonatal Intensive Care Unit (NICU). Study Design: Prospective observational study. Place and Duration: The study was conducted at the Department of Pediatrics Liaquat University of Medical & Health Sciences (LUMHS) Jamshoro Pakistan, from May 2025 to May 2026. Methodology: This prospective observational study included 120 neonates aged 0 to 28 days of either sex who presented with clinically diagnosed neonatal seizures and were followed until hospital discharge. Data were collected using a pretested semi-structured questionnaire that included demographic characteristics, seizure profile, antenatal, natal, and postnatal history, clinical examination findings, laboratory investigations, treatment, and clinical outcomes. Seizures were classified according to Volpe’s classification. Data were analyzed using descriptive statistics in Microsoft Excel. Results: During the study period, 600 neonates were admitted to the NICU, of whom 120 had neonatal seizures, giving a frequency of 20.0%. Of the affected neonates, 77 (64.2%) were male and 43 (35.8%) were female. Eighty-four (70.0%) were term neonates, while 36 (30.0%) were preterm. Seizures developed within the first 24 hours of life in 35 (29.2%) neonates and between 24 and 48 hours in 43 (35.8%) neonates. At discharge, 98 (81.7%) neonates survived, whereas 22 (18.3%) died, resulting in an overall mortality rate of 18.3%. Conclusion: Neonatal seizures were observed in one-fifth of NICU admissions and were associated with considerable mortality. Birth asphyxia was the leading underlying cause. Early recognition, prompt diagnosis, and appropriate management may improve clinical outcomes and reduce neonatal mortality.